Rasio Sdm Pengawas (Inspektor) Kelaikan Pesawat Udara Terhadap Beban Tugas Keselamatan Penerbangan - Wahyoe, Wahyoe (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
To realize the safehJ of air transport.ation, the government needs to do a monitoring of the ainvorthinessof aircraft. therefore, the Directorate General of Air Transportation Directorate of the Ministn; ofTransportation formed a special deal with it is the Directorrzte of Ainuorthiness and Operation ofAircraft. The purpose of this study is to determine the number of inspectors required for the supennsionof ainvorthiness of aircraft to follmu the deuelapnient of the number of aircraft operated. By usinga simple linear formuli:l., the number of aircraft inspedor personnel can be done m; making use ofequation Y = -11.04 + 108 X.